Improving photovoltaic performance through doped graphene heterostructure modules - Mansi Rana; Preetika Sharma (Chemical Physics Impact)
To improve the efficiency of conventional silicon photovoltaic (PV) cells, silicon is being replaced by graphene material which not only reduces the reflectance of solar energy but also supports full spectrum solar coverage. In this design, both n-type and p-type silicon layers in the PV cell are replaced by doped graphene layers. Nitrogen (N) doped graphene in n-type layer and boron (B) doped graphene in p-type layer are incorporated as n-type and p-type layer in PV cell. N-type materials enhance the conductivity of a semiconductor by increasing the number of available electrons while p-type materials increase conductivity by increasing the number of holes present in the semiconductor. This structure is then studied for its electronic properties such as band structure (BS), density of states (DOS), projected density of states (PDOS) and geometrical stability using density functional theory (DFT) implemented in Quantum ATK (Synopsis) (P-2019.03-SP). Additionally, its potential for high power conversion efficiency (ŋ), fill factor (FF), and maximum power output (Pmax) is evaluated using the one-diode model in MATLAB. The results obtained are varied for changes in temperature (T) and solar irradiance (G). For instance, at T = 25 °C and G = 1000 W/m², conventional silicon PV cells achieve a maximum power output (Pmax) of 233.8066 W, fill factor (FF) of 76.04 %, and η of 19.21 %. In contrast with graphene based PV cell, a Pmax of 258.9621 W, FF of 84.62 % and η of 21.29 % are obtained. It can be concluded that graphene in layers of a PV cell can act as an ideal energy conversion system to promote various optoelectronic devices such as light-emitting diodes and photodetectors.